The effect of the basic tillage system on soybean weediness in the right-bank Forest-Steppe of Ukraine - Zadorozhnyi, V.; Chernelivska, O.; Zadorozhnyi, A.; Sokulskyi, M.; Labunets, A. (Quarantine and plant protection, 2023)
Goal. To improve the system of soybean crops weed control under different methods of tillage. Methods. Field and laboratory experiment, mathematical and statistical method to assess the reliability of the obtained results. Results. The researched species composition of weeds in soybean crops included 12 species of 7 families, with a predominance of dicotyledonous species (80.1—93.3%), regardless of the tillage method the proportion of the monocotyledonous species made up 6.7—19.9%. The following species were most common: Chenopodium album L., Amaranthus retroflexus L., Polygonum lapathifolia L., Galinsoga parviflora Cav., Echinochloa crus-galli (L.) Pal. Beauv. and Setaria glauca (L.) Pal. Beauv. The maximum weediness of soybean crops before herbicides application was observed under the moldboardless main tillage use (to a depth of 10—12 cm) and amounted to 481.5 pcs./m2, of which dicotyledonous species made up 81.7% and monocots — 18.3%. The lowest number of weeds (at the level of 254 pcs./m2) was observed under the No-till technology, the share of dicot species made up 80.1%. With the use of the moldboard tillage in soybean crops before herbicides use, the total number of weeds was 425.5 pcs./ m2, where annual dicotyledonous species predominated (93.3%). Soybean crops subject to herbicides use on the moldboard tillage variant formed a 2.49 t/ha yield, which was 50% higher than that of the weeded control variant. The use of the moldboardless tillage and No-till technology ensured productivity in the range of 2.34—2.40 t/ ha. Conclusions. Regardless of the soil tillage method, dicotyledonous weed species occupied from 80.1 to 93.3% of the soybean crops, with the predominance of Chenopodium album L., the share of which was 66.6—77.3% and Polygonum lapathifoliа L. — 17.6—24.9%. The use of various methods of soil tillage and weed control ensures elimination of weeds at the level of 91.0—91.5% and maintaining productivity in the range of 45—50%.